Imperial Gateway : Colonial Taiwan and Japan's Expansion in South China and Southeast Asia, 1895–1945 - Shirane, Seiji, 1982- (Book collections on Project MUSE., 2022)
"Drawing on multilingual archives from six countries, this book examines the strategic importance of Taiwan to the Japanese Empire and uncovers the half-century of dynamic relations between Japan, Taiwan, China, and Western regional powers in an ever-shifting international order"--